LANDASAN HUKUM PEMBERIAN HAK WILAYAH PESISIR DAN PULAU TERHADAP MASYARAKAT ADAT DI PROVINSI KEPULAUAN RIAU - Eldi Eldi (Jurnal Inovasi Penelitian, 2020)
The aim of this article is to anlyze the legal basis of granting coastal and island territory to indigenous people in the Province of Riau to connected with the issuance of legislation on the management of coastal areas and small islands in the provisions of regulation Number. 27/2007 and the rights of local coastal waters and small islands according to goverment regulation Number 40/1996, especially in clause of 60 starting for granting of business rights, building rights and land rights that are entirely island or bordered by the beach are governed by the goverment regulation and it’s regulation. In this article used the normative juridical methodology, the author used in this article study of references that conducted used secondary data, namely collecting data from various literature from the law, books, documents and archieves related to this issue. Thus, the analysis used by collecting data to be processed and analyzed according to the nature of the collected data, for futher presented by the analyst evaluative. This scientific writing shows that the rights of the coastal water exploitation contained in regulation Number 27/2007 abaout PWP3K is one of legal norms governing coastal, but it turns out to cause pros and cons.